The Use of Macromedia Flash Player as Media in Enhancing Students’ Writing Ability in the 1st Year Students of SMAN 1 Pinrang - Khaeril Amri (English Lecturers and Teachers Association (ELTA), 2022)
This research was about the use of flash player as media in enhancing students’ writing ability in descriptive text at the 1st year students of SMAN 1 Pinrang. The principle problem was only one that was “To what extend does flash player as media enhance the students’ writing ability in writing descriptive text at the first year students of SMAN 1 Pinrang?” The objective of the research is “to find out the enhancement of the students’ writing ability in writing descriptive text”.The research was quasi Experimental Design using “Nonequivalent Control Group Design. The population of this research was the 1st year students of SMAN 1`Pinrang which consisted 270 students. The samples were taken by using cluster samping. The researcher took two classes randomly as the sample. It involved 60 students with X.2 consisted 30 students as experiment class and X.4 consisted 30 students as control class. In experiment class, the total mean score of post-test was 70.06 was greater than the total mean score in control class was 62.96. From the t-test, the researcher found that the value of t-test in post-test was greater than t-table (3.22 > 2.021). Based on the finding and discussion of the research, the researcher drew a conclusion that the use of flash player as media is effective to enhance the students writing ability in descriptive text at the first year students of SMAN 1 Pinrang. Keywords: Teaching writing, Macromedia flash player, Students writing ability